2007
DOI: 10.1111/j.1469-7610.2007.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and posttraumatic stress disorder in delinquent female adolescents

Abstract: Incarcerated young females in Japan have serious trauma-related problems, and the degree of depression is a strong predictor of PTSD development and symptoms. This study highlights the importance of adequate diagnosis and treatment of PTSD in delinquent female adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 29 publications
(37 reference statements)
1
41
0
Order By: Relevance
“…Girls tended to have more frequent symptoms than boys, however, especially for reexperiencing and hyperarousal (Brosky and Lally 2004). Among two large samples of adolescent female juvenile offenders, 33-37% had PTSD and 55-77% of these cases were precipitated by sexual abuse (Ariga et al 2008;Dixon et al 2005). Among incarcerated youth, nearly all of whom were exposed to a violent act, 28% of boys and 52% of girls met criteria for PTSD (Wood et al 2002).…”
Section: Ptsd and Maltreatment: Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation
“…Girls tended to have more frequent symptoms than boys, however, especially for reexperiencing and hyperarousal (Brosky and Lally 2004). Among two large samples of adolescent female juvenile offenders, 33-37% had PTSD and 55-77% of these cases were precipitated by sexual abuse (Ariga et al 2008;Dixon et al 2005). Among incarcerated youth, nearly all of whom were exposed to a violent act, 28% of boys and 52% of girls met criteria for PTSD (Wood et al 2002).…”
Section: Ptsd and Maltreatment: Epidemiologymentioning
confidence: 97%
“…Many symptoms related to PTSD in maltreated youth mimic these disorders-such as impulsivity, labile mood, dysphoria, social withdrawal, difficulty concentrating, restlessness, and irritability-which can lead to misdiagnosis and inappropriate interventions. The presence of trauma symptoms can complicate treatment for other problems as well (Ariga et al 2008;Dixon et al 2005;Ford et al 2000;Schumacher et al 2006;Stevens et al 2003;Titus et al 2003;Weinstein et al 2000).…”
Section: Ptsd and Maltreatment: Symptomatology And Outcomementioning
confidence: 98%
“…To illustrate, samples of justice involved youth across diverse settings have revealed that 33% of Japanese female juvenile offenders (Ariga et al 2008), 27% of Swiss male juvenile offenders (Urbaniok et al 2007), and 10-19% of detained youth in the United States (Abram et al 2004;Cauffman et al 1998;Ford et al 2008;Steiner et al 1997) meet criteria for PTSD. By comparison, in the United States (Copeland et al 2007;Mongillo et al 2009), PTSD is rare among young (ages 0-4) children (0.6% prevalence) and school-age children (1% prevalence), but more common among adolescents (5% prevalence) (Kilpatrick et al 2003).…”
mentioning
confidence: 99%
“…Research shows children who are affected by parental incarceration experience anxiety, depression, fear and guilt) [4][5][6][7][8]31,44,50]. Furthermore these problems are linked to low self-esteem, learning difficulties and disruptive behavior.…”
Section: Explored Developmental Theoriesmentioning
confidence: 99%
“…Perusing this issue, may reveal that as a parent walks into prison, their children simultaneously walk into a revolving door of multiple dilemmas linked to psychological challenges, behavioral difficulties, and emotional/ cognitive issues. Researchers have revealed that children who have a parent in prison are linked to many negative outcomes unfortunately [1][2][3][4][5][6][7][8]. This highlights the importance of the ripple effect of having an incarcerated parent.…”
Section: Purpose Of Research Introductionmentioning
confidence: 99%